Education Management and Information System (EMIS) for Public Elementary Schools (International Journal of Scientific Research and Management (IJSRM), 2018)
Educational Management Information System (EMIS) in Public Elementary School Abstract - The study was conducted to determine the extent of effectiveness on the implementation of Education Management Information System (EMIS) as part of educational management functions in public elementary schools of Surigao Del Sur Philippines. Descriptive survey method using a researcher-made questionnaire was used. The respondents of the study were nine selected public elementary schools from the three clusters of Surigao Del Sur Division. Findings revealed that from the eight (8) modules of EMIS, Pupil MIS received the highest mean while Finance MIS obtained the least as to the implementation of EMIS Modules. Planning and monitoring were found to be high as to the level of effectiveness of EMIS in public elementary schools. The study concludes that most of the public schools in Surigao Del Sur Division, regardless with its type, effectively implements EMIS Modules. However, Finance MIS requires further enrichment on planning, implementation, and evaluation. Hence, the study recommends strengthening of EMIS modules particularly on Finance MIS and establishment of sustainable EMIS by sharing the best practices in implementing the EMIS of the different schools. Keywords: Educational Management Information System (EMIS), EMIS Modules, EMIS Implementation, EMIS Effectiveness, School Performance